2008
DOI: 10.1055/s-2008-1076736
|View full text |Cite
|
Sign up to set email alerts
|

Different Clinical and Immunological Presentation of Ataxia-Telangiectasia within the Same Family

Abstract: Ataxia-telangiectasia is a rare multisystem neurodegenerative genetic disorder due to mutation of ATM gene. The clinical expression and the immunological abnormalities are variable and apparently not associated with the type of ATM mutations. We report on two siblings affected by A-T with different clinical and immunological presentations; in particular in one the immunological phenotype was reminiscent of hyper IgM syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 8 publications
2
20
0
1
Order By: Relevance
“…Another characteristic finding reported in this study was the presence of absolute CD4 lymphocytopenia. Similar cases have also been reported from Israel, Italy and Iran [2][3][4].…”
supporting
confidence: 82%
“…Another characteristic finding reported in this study was the presence of absolute CD4 lymphocytopenia. Similar cases have also been reported from Israel, Italy and Iran [2][3][4].…”
supporting
confidence: 82%
“…In fact, 1 patient was initially diagnosed with female HIGM syndrome with mild ataxia. Recent study has shown the immunological phenotype could be reminiscent of hyper-IgM syndrome in patients with AT [27,39], and our study has shown the hyper-IgM phenotype is not rare in the patients.…”
Section: Discussionmentioning
confidence: 55%
“…The clinical and immunological presentation of ataxiatelangiectasia may differ even within the same family, as described by Soresina et al [1]. Most patients tend to be wheelchair bound by their second decade.…”
Section: Discussionmentioning
confidence: 73%